2014
DOI: 10.3109/01658107.2014.953697
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-ophthalmological Features of Cerebral Venous Sinus Thrombosis

Abstract: Neuro-ophtalmological symptoms of 49 patients with cerebral venous sinus thrombosis and different onset of the disease were evaluated. Papilloedema was revealed in 84.6% of patients with acute and subacute onset of the disease and in all patients with chronic onset. Visual disturbances due to papilloedema and postpapilloedema optic atrophy were found in 65.2% of patients with chronic onset. Patients with acute onset of cerebral venous sinus thrombosis were successfully treated with local endovascular thromboly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Coutinho et al ( 2014 ) found that papilledema was more common in patients with cortical hemorrhage (44 vs. 9%) than in those without. Eliseeva et al ( 2015 ) conducted a retrospective case study of 49 patients diagnosed with CVT, including 15 who were acute (30.6%), 11 who were subacute (22.4%) and 23 who were chronic (47.0%). Papilledema was observed in 84.6% of the CVT patients with acute and subacute onset, and all patients with chronic onset had papilledema.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Coutinho et al ( 2014 ) found that papilledema was more common in patients with cortical hemorrhage (44 vs. 9%) than in those without. Eliseeva et al ( 2015 ) conducted a retrospective case study of 49 patients diagnosed with CVT, including 15 who were acute (30.6%), 11 who were subacute (22.4%) and 23 who were chronic (47.0%). Papilledema was observed in 84.6% of the CVT patients with acute and subacute onset, and all patients with chronic onset had papilledema.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[ 5 ] It typically affects the superior sagittal and transverse sinus more frequently. [ 6 ] As CVT presents in various locations, its clinical manifestation also presents various symptoms depending on the location and mimics other disorders. Diagnosing CVT is challenging and takes an average of several days [ 7 ] owing to its low incidence and nonspecific symptoms, including headache, nausea, vomiting, and altered consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…DVST should be suspected in all patients with papilledema as it can present in a very similar manner to IIH as was seen in Case 1. 3,8 All cases of DVST should be investigated for an underlying hypercoagulable state, which is likely to be present in most patients. We found that only 2 out of 15 patients in our series (13%) had no identifiable prothrombotic factors.…”
Section: Discussionmentioning
confidence: 99%